Multifunctional coating based on EPC-specific peptide and phospholipid polymers for potential applications in cardiovascular implants fate. Issue 48 (21st November 2016) - Chen, Huiqing; Zhao, Yuancong; Xiong, Kaiqin; Li, Jingan; Chen, Jiang; Yang, Ping; Huang, Nan
Abstract : Surface biofunctional modification of cardiovascular implants via the conjugation of biomolecules to prevent thrombosis and restenosis formation and to accelerate endothelialization has attracted considerable research interest. Abstract : Surface biofunctional modification of cardiovascular implants via the conjugation of biomolecules to prevent thrombosis and restenosis formation and to accelerate endothelialization has attracted considerable research interest. In this study, we aimed to develop a multifunctional surface that could exhibit good hemocompatibility and function well in inducing desirable vascular cell–material interactions. The multifunctional coating (PCDLOPTPT@Ti), containing phosphorylcholine groups and endothelial progenitor cell (EPC)-specific peptides (PT), was prepared on titanium (Ti) surfaces via chemical conjugation. The results of platelet adhesion, activation, fibrinogen denaturation, and whole blood dynamic adhesion testing indicated that the PCDLOPTPT@Ti coating presented a better hemocompatibility when compared with bare Ti and other control samples. In vitro EPC and smooth muscle cell (SMC) cultures showed that the PCDLOPTPT@Ti coating significantly promoted the adhesion and proliferation of EPCs and inhibited the attachment and proliferation of SMCs. In vivo animal tests further confirmed that the PCDLOPTPT@Ti coating effectively inhibited thrombus formation and intimal hyperplasia while supporting endothelium regeneration. These results effectively suggest that the PCDLOPTPT@Ti coating may be promising as a coating on cardiovascular implants.